People starting the 1986 y-Walk - Brock, Trish (photographer):::Creator:::
Negative shows a large crowd of men and women walking towards the starting line for the y-Walk in 1986. They are leaving from a parking lot and a few of the people are carrying balloons. There is one little girl visible in the crowd.